Determinação de valores energéticos do resíduo de cervejaria e do bagaço de azeitona para frangos de corte - Adams, Carine Beatriz (2022)
The economic efficiency of the poultry industry has been pressured due to the high costs of ingredients, which result in higher production costs. Residues from the food industry are seen as potential alternatices to be used in animal nutrition, also contributing to the sustainability of the systems. Brewery waste and olive pomace can be potential ingredients in poultry nutrition, contributing to regional development, since they are produced in large quantities in Rio Grande do Sul. For an ingredient to be used in poultry nutrition without negatively affecting production performance, it is necessary to know its nutritional composition and apparent metabolizable energy values (AME). A study was conducted at the UFSM Poultry Laboratory with the objective of determining the AME, corrected AME for nitrogen balance (AMEn) and ileal digestible energy (IDE) of dehydrated brewery waste (DBW) and olive pomace (OP), through the regression method. A total of 320 one-day-old chickens were housed in metabolic cages, receiving water and feed at will, and the same initial diet. At 14 days, the birds were weighed and 280 chickens were distributed into 40 cages according to average weight. From 14 to 21 days, the chickens received 5 experimental diets, in 8 replicates of 7 chickens each. The diets consisted of a reference diet and four test diets, two containing 10 or 20% brewery waste and two diets containing 7.5 or 15% olive pomace. The test ingredients partially replaced the energy source ingredients in the feed (corn, soybean meal, and soybean oil). On days 19 and 20 partial excreta collections were performed and on day 21 the birds were weighed and ileal content was collected. The apparent ileal digestibility coefficients and metabolizability of DM, N and energy were calculated. There was a linear (p<0.05) decrease in body weight, body weight gain and feed intake when DBW or OP was included in the reference diet. The regressions obtained were: AME= 2.935x + 7.739; AMEn= 2.785x + 11.302 and IDE= 2.524x + 16.366 for the diet with DBW; while AME= 1.778x + 7.739; AMEn= 1.581x + 11.302 and IDE= 1.394x + 16.366 were obtained for the diet with OP (p<0.05). Thus, the AME and AMEn values of DBW for broiler chickens were 2,935 and 2,785 kcal/kg DM, respectively, AME and AMEn of OP were 1,778 and 1,581 kcal/kg DM, respectively. The IDE for brewery residue was 2,524 kcal/kg DM and for olive pomace was 1,394 kcal/kg DM. Therefore, this determination can provide useful information that helps to improve the use of alternative ingredients in broiler diets, formulating precise diets to meet the requirements of chicken.